Christian Thodberg: En glemt dimension i Grundtvigs salmer - Lindhardt, Poul Georg (Grundtvig-studier, 1970)
Christian Thodberg, En glemt dimension i Grundtvigs salmer - bundetheden til dåbsritualet.Rev. by. P. G. Lindhardt.When Grundtvig’s hymns became part of the national heritage no longer identified with Grundtvigian preaching, the dimension of his hymns fell into oblivion which Dr. Thodberg has rediscovered and given evidence for in this book. It is a marvellous discovery, and as such it has the character of something self-evident. Divine service and its ceremonies remain the background of the hymns. As a clergyman Grundtvig felt deeply committed to rituals, not because of liturgical formalism or an interest in “cult”. Because of the character of personal address of the liturgical act he tried to find a “particular word” as an approach to Christianity.The investigation is centered upon Grundtvig’s attitude to the baptismal ritual that was authorised in 1783. He was quite happy that he was one of the first to have been baptised according to it, and Thodberg shows that wherever he touches upon baptism in his hymns, Bishop Balle’s ritual underlies his thought. The outline of this ritual recurs in the hymn “ Op til Guds hus vi gå” (Den danske Salmebog, 376); but the point is further illustrated by a wealth of detail from Grundtvig’s Sang-Værk, even from the less well known parts of it. A comparison with the baptismal ritual of 1912, which was influenced by various revival movements, is inescapable, and it is emphasized (both by the author and by the reviewer) that the Gospel underlying the baptismal ritual of 1912 is St. Matthew 28.19- 20, whereas with Balle and Grundtvig it is the Gospel about Christ taking the children up in his arms and blessing them. This “old” gospel of baptism was mutilated in 1912 by the deletion of the opening passage about the disciples’ reaction to the “superstitious” mothers and Christ’s indignation at this reaction. It is one of Thodberg’s merits to have shown the close connection in the hymns between the Lord’s Prayer and the words “he took them up in his arms”.This made the Lord’s prayer the proper prayer for children, and baptism a consequence of it. This little book is unusually weighty. Apart from being an intervention in current debate it is a learned and congenial piece of genuine Grundtvig scholarship. We look forward to a new study on Grundtvig’s communion hymns, on which Dr Thodberg is working, with the greatest expectations.